METABOLIC SYNDROME IN PATIENTS WITH LUPUS NEPHRITIS : Running title : Metabolic syndrome in lupus nephritis - Rabrenović, Dr sc. med. Violeta; Petrovic, Milica; Rabrenovic, Milorad; Rancic, Nemanja (Journal of Medical Biochemistry, 2024)
SUMMARY Background: Metabolic syndrome (MetS) in the patients with SLE represents an additional burden and a poor prognostic factor for the onset or worsening of atherosclerosis and cardiovascular complications. In many patients with lupus nephritis (LN) MetS is often already manifested initially. Our work aimed to determine the frequency and characteristics of MetS in patients with LN, as well as the relationship components of MetS and characteristics of disease activity Methods: The clinical study included 67 patients with LN, 54 (80.6%) female and 13 (19.4%) male, average age 42.86±14.46. Patients were divided into two groups: with MetS (35.8%) and without MetS (64.2%), active LN had (34 or 50.7%) and LN in remission (33 or 49.2%). We monitored clinical and biochemical parameters of interest. Results: Comparing patients with LN collectively, as well as those with MetS and without MetS, we observed that patients with MetS were older (p=0.001), BMI (p<0.001) and systolic arterial pressure was higher (p=0.002) and smokers were more common in this group (p<0.001). In the analysis, increased triglycerides (p<0.001) and creatinine (p=0.027), and decreased albumin (p=0.050) and GFR (p=0.020) were observed in the group with MetS. MetS was present in 44.1% of patients with active LN and in 27.7% with LN in remission. The most common MetS parameter was arterial hypertension (76.6%), which correlated with GFR and creatinine; hypertriglyceridemia (47.8%) which is correlated with anti ds DNA Ab, erythrocyturia, proteinuria and SLEDAI/r index; decreased HDL cholesterol (28.4%) which significantly correlated with albumin, C3 and anti ds DNA Ab. Conclusions: In our patients with LN, MetS was associated with older age, impair kidney function and smoking. The most common parameter of MetS was arterial hypertension and dyslipidemia, which were significantly correlated with disease activity parameters, indicating an increased risk of cardiovascular complications in this group of patients.